Results of Non-contrast Brain Computed Tomography Scans of 1-18 Year Old Epileptic Children - FALLAH, Razieh; NAFISI MOGHADAM, Reza; FALLAH TAFTI, Mohammad; SALMANI NODOUSHAN, Mahdi (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Fallah R, Nafisi Moghadam R, Fallah Tafti M, Salmani Nodoushan M. Results of Noncontrast Brain Computed Tomography Scans of 1-18 Year Old Epileptic Children. Iran J Child Neurol 2012; 6(3): 33-38. Objective The advent of computed tomography (CT) scan revolutionized the diagnosticevaluation of neurologic patients. The aim of this study was to evaluate brain CTresults of epileptic children. Materials & Methods In a descriptive cross-sectional study, noncontrast brain CT scan of 150 consecutive1-18 year old epileptic children whom were referred to pediatric neurology clinic ofShahid Sadoughi University of Medical Sciences, from May 2008 to October 2010 inYazd-Iran, evaluated. Results Sixty two girls and 88 boys with mean age of 6.6 ± 4.3 years were evaluated.In 38 (25.3 %) children, seizure onset age was under one year and 38 others hadabnormal mental / developmental status. Fifty three children (35.3 %) and 97 (64.7%)had partial and generalized seizures, respectively. Partial seizures were more prevalentin children with seizure onset in < 1 year [41.5% (22/53) vs. 16.5% (16/97)] Result of CT was normal in 74 % (n=111). Among the patients with abnormalresults, 18(46%) had brain atrophy, 10 (25.6%) structural CNS dysgenesia, six (15.4%)intracranial calcification, three (7.8%) hydrocephaly and two had (5.2%) brain tumor.Abnormal brain CT was more prevalent in patients with seizure onset in less than oneyear of age [60.5% (23 of 38) vs. 14.3% (16 of 112), p = 0.003], partial epilepsy [51% (27of 53) vs. 12% (12/97)], and abnormal developmental status [ 81.5% (31 of 38) vs.7% (8of 112]. Mean age of seizure onset in epileptic children with abnormal brain CT scanwas less (M ± SD:1/17 ± 0.6 years versus 4.02±1.9 years). Conclusion Brain CT scan might be considered in evaluation of epileptic children with partialseizures, seizure onset in less than one year of age or neurodevelopmental delay. References Jagoda A, Gupta K. The emergency department evaluationof the adult patient who presents with a first-time seizure.Emerg Med Clin North Am 2011; 29(1):41-9. Camfield PR, Camfield CS. Pediatric epilepsy. In:Swaiman KF, Ashwal S, Ferriero D M. Pediatric Neurology: principles & practice. (4th ed). Philadelphia:Mosby Elsevier, 2006.P. 983. Gaillard WD, Chiron C, Cross JH, Harvey AS, Kuzniecky R, Hertz-Pannier L, Vezina LG; ILAE, Committee for Neuroimaging, Subcommittee for Pediatric. Guidelines for imaging infants and children with recent-onset epilepsy. Epilepsia 2009; 50(9):2147-53. Soto-Ares G, Jissendi Tchofo P, Szurhaj W, Trehan G,Leclerc X. Management of patients after a first seizure. J Neuroradiol 2004; 31(4):281-8. (in French) Hirtz D, Ashwal S, Berg A, et al. Practice parameter:evaluating a first nonfebrile seizure in children: report of the quality standards subcommittee of the American Academy of Neurology, the Child Neurology Society, and the American Epilepsy Society. Neurology 2000; 55:616– 623. Kuzniecky RI. Neuroimaging in pediatric epilepsy.Epilepsia 1996; 37, Suppl 1:S10-21. Adamsbaum C, Rolland Y, Husson B. Pediatric neuroimaging emergencies. J Neuroradiol 2004;31(4):272-80. (in French) Proposal for revised classification of epilepsies and epileptic syndromes. Commission on Classification and Terminology of the International League Against Epilepsy. Epilepsia 1989; 30:389–399. Hsieh DT, Chang T, Tsuchida TN, et al. New-onset afebrile seizures in infants: role of neuroimaging.Neurology 2010;12:74(2):150-6. Khodapanahandeh F, Hadizadeh H. Neuroimaging inchildren with first afebrile seizures: to order or not toorder? Arch Iran Med 2006;9(2):156-8. Berg AT, Testa FM, Levy SR, Shinnar S. Neuroimaging in children with newly diagnosed epilepsy: A community based study. Pediatrics 2000; 106(3):527-32. Maytal J, Krauss JM, Novak G, Nagelberg J, Patel M. Therole of brain computed tomography in evaluating children with new onset of seizures in the emergency department.Epilepsia 2000; 41(8):950-4. Kumar R, Navjivan S, Kohli N, Sharma B. Clinicalcorrelates of CT abnormality in generalized childhood epilepsy in India. J Trop Pediatr 1997;43(4):199-203. Aguilar-Rebolledo F, Sosa-Villalobos R, del Castillo- Troncoso C. Should computed axial tomography of theskull be done in all pediatric patients with epilepsy?. BolMed Hosp Infant Mex 1992;49(12):845-50. (in Spanish) Obajimi MO, Fatunde OJ, Ogunseyinde AO, OmigbodunOO, Atalabi OM, Joel RU. Computed tomography and childhood seizure disorder in Ibadan. West 2004;23(2):167-72. Wammanda RD, Anyiam JO, Hamidu AU, Chom ND,Eseigbe EE. Computerized tomography of children with seizure disorders. Niger J Clin Pract 2009;12(1):25-8. Korff C, Nordli DR Jr. Do generalized tonic-clonic seizures in infancy exist? Neurology 2005, 65:17501753. Vanderver A, Chang T, Kennedy C, et al. MR Imaging forthe diagnosis of cerebral dysplasia in new onset seizuresin children. Ann Neurol 2003,54:S114.